Traffic safety strategies - Sadauskas, Vigilijus (Transport, 2003)
Fast development of the number of vehicles is closely related not only to large benefit for the public but also to certain undesirable social and economic consequences. Firstly – large numbers of injured and killed people are involved into the accidents. The target to improve traffic safety situation in Lithuania can be reached only after the detailed evaluation of transport system, environment, traffic participants, road and vehicle. Taking into consideration the accident situation in Lithuania and its causes the followings priority trends are suggested: The improvement of the coordination of road traffic safety system, the training and education of road users, the explanation of the importance of traffic safety and its propagation, the improvement of traffic conditions. Recommendations and proposals for differentiated criterion of maximum speed limit selection taking into account different factors are provided in the work.First Published Online: 19 Dec 2011